2020
DOI: 10.1186/s12888-020-02645-6
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety, and burnout among medical students and residents of a medical school in Nepal: a cross-sectional study

Abstract: Background: Medical students and residents were found to have suffered from depression, anxiety, and burnout in various studies. However, these entities have not been adequately explored in the context of Nepal. We proposed to determine the prevalence of depression, anxiety, burnout, their associated factors, and identify their predictors in a sample of medical students and residents in a Nepalese medical school. Methods: It was a cross-sectional study with 651 medical students and residents chosen at random b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
92
3
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(116 citation statements)
references
References 88 publications
7
92
3
14
Order By: Relevance
“…Our study found the prevalence of burnout to be considerably higher than a previous study conducted in Nepal which reported the prevalence to be 48.8% [23]. This disparity in results could be due to the different instruments (CBI vs. OLBI) used to measure burnout.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Our study found the prevalence of burnout to be considerably higher than a previous study conducted in Nepal which reported the prevalence to be 48.8% [23]. This disparity in results could be due to the different instruments (CBI vs. OLBI) used to measure burnout.…”
Section: Discussioncontrasting
confidence: 95%
“…Some students might have joined medical school under parental or peer pressure, or with the desire for higher socioeconomic status. They may become demotivated after knowing the reality of medicine and develop more negative attitudes towards medicine as a career [ 23 , 38 , 39 ]. Hence, they may be more likely to develop burnout in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…Since the answer “other” was closed ended it is not possible to determine to what extent respondents included psychological disorders into that category. It would be interesting for future studies to further investigate the prevalence of psychological conditions among osteopathy students [ 52 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of psychological illnesses including anxiety, burnout, and depression is high among medical students. 4 The common reasons for high stress and anxiety included the pressure of passing exams, the pressure of living up to family's expectations, fear of stepping into the real world of medicine. 5 Furthermore, the long-term lockdown due to COVID-19 pandemic caused further worsening in the psychological and learning behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Medical education is long and physically and emotionally demanding. 4 It feels like you have been studying for so long and yet you are so far from becoming a doctor. But, it is this year that gave us the signal of being close to the destination.…”
Section: Introductionmentioning
confidence: 99%